Fertilization, but Not Post-Implantation Development, Can Occur in the Absence of Sperm and Oocyte Beta1 Integrin in Mice - Mimouni, Nour El Houda; Ialy-Radio, Côme; Denizot, Anne-Lyse; Lagoutte, Isabelle; Frolikova, Michaela; Komrskova, Katerina; Barbaux, Sandrine; Ziyyat, Ahmed (International journal of molecular sciences, 2022)
Fertilization is a complex process that requires successive stages and culminates in the adhesion/fusion of gamete membranes. If the question of the involvement of oocyte integrins has been swept away by deletion experiments, that of the involvement of sperm integrins remains to be further characterized. In the present study, we addressed the question of the feasibility of sperm-oocyte adhesion/fusion and early implantation in the absence of sperm β1 integrin. Males and females with β1 integrin-depleted sperm and oocytes were mated, and fertilization outcome was monitored by a gestational ultrasound analysis. Results suggest that although the sperm β1 integrin participates in gamete adhesion/fusion, it is dispensable for fertilization in mice. However, sperm- and/or oocyte-originated integrin β1 is essential for post-implantation development. Redundancy phenomena could be at the origin of a compensatory expression or alternative dimerization pattern.
Keywords: interakce spermie a vajíčka; Male; oocyty; Integrins; Fertilization; antigeny CD29; integriny; Spermatozoa; mužské pohlaví; Sperm-Ovum Interactions; sperma; Semen; Animals; ženské pohlaví; zvířata; spermie; myši; Integrin beta1; Mice; Female; fertilizace; Oocytes